The fusing ability of sperm is bestowed by CD9-containing vesicles released from eggs in mice - Miyado, Kenji (National Academy of Sciences, 2008)
Membrane fusion is an essential step in the encounter of two nuclei from sex cells—sperm and egg—in fertilization. However, aside from the involvement of two molecules, CD9 and Izumo, the mechanism of fusion remains unclear. Here, we show that sperm–egg fusion is mediated by vesicles containing CD9 that are released from the egg and interact with sperm. We demonstrate that the CD9(−/−) eggs, which have a defective sperm-fusing ability, have impaired release of CD9-containing vesicles. We investigate the fusion-facilitating activity of CD9-containing vesicles by examining the fusion of sperm to CD9(−/−) eggs with the aid of exogenous CD9-containing vesicles. Moreover, we show, by examining the fusion of sperm to CD9(−/−) eggs, that hamster eggs have a similar fusing ability as mouse eggs. The CD9-containing vesicle release from unfertilized eggs provides insight into the mechanism required for fusion with sperm.